RESPON PEMBERIAN PUPUK PETRAGONIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI BOTOL (Brassica rapa var. parachinensis L) DALAM POLYBAG - Badrul Ainy Dalimunthe (UNIVERSITAS LABUHANBATU, 2019)
The design used was a single randomized block design with the dosage of petroganic fertilizer ie: treatment (O0: 0 g / plant, O1: 5 g / plant, O2: 5.5 g / plant and O3: 6 g / plant). Parameters observed were: number of plant leaves (strands), plant leaf area (cm), wet weight of plant (g). The results of this study can be concluded that: 1.Response of Petroganik fertilizer to the number of leaves of mustard plant (Bransissca rapa var.parachinensis) In polybags has no significant effect. 2. The response of Petroganic fertilizer to the area of leaves of the mustard greens (Bransissca rapa var.parachinensis) is seen to have an effect on the real possibility in this observation. Petroganic fertilizers have the right elements in the leaf enlargement such as N. 3. Response of Petroganic fertilizer to wet weight of mustard plant (Bransissca rapa var.parachinensis) Does not seem to influence significantly and even the excessive dosage giving the weight of the plant is less likely to be in this case the nutrient in the fertilizer becomes the residue to the plant so that the mustard plant is poisoned resulting in decreasing the weight of the plant Keywords: Bottled Bottom, Petroganic Fertilizer.